Strategi Pengelolaan Kelas Sebagai Upaya Meningkatkan Pembelajaran Aktif - Saepulloh, Asep; Yuniar, Dianti; Holik, Abdul (Jurnal Ilmiah Wahana Pendidikan, 2024)
The purpose of this study is to improve active learning through classroom management. The method and type of data collection in this study is by library research by collecting books, journals and previous research results that support the research theme. This research data analysis technique uses a descriptive analysis approach. The stage begins with reducing data from library sources, then organizing and presenting data, verifying then ending with concluding data to answer the problem formulation. The results of the study concluded that First Classroom Management is the teacher's skill to create and maintain optimal learning conditions, and control them when there is a disruption in the teaching and learning process. Both active learning are the result of joint design between teachers (trainers) and students (learners). The first step, teachers create a climate that allows the learning process to occur optimally. The next step, the teacher together with the students agree on the lesson plan to be implemented. Classroom Management Strategies in learning must increase effectiveness in student learning, including; 1. Creating an optimal classroom atmosphere or conditions. 2. Trying to stop deviant student behavior. 3. Creating Work Discipline. 4. Creating harmony between teachers and students